Effect of Mind Mapping on Creative Thinking of Children in Scratch Visual Programming Education. (July 2022) - Su, Yu-Sheng; Shao, Mingming; Zhao, Li
Scratch, a kind of visual programming software, has been widely used in instruction for primary school children. Scratch constructs a digital world for children to design, develop, and create coursework in which their creative thinking is fostered. Different instructional methods have been designed and implemented to stimulate children's creative thinking skills through their coursework. This study investigated whether scaffolding construction with mind mapping promoted children's creative thinking in a Scratch course. Two groups of 84 fifth-grade pupils participated in the study. The experimental group of 44 students adopted the scaffolding construction with mind mapping in the Scratch course, while the control group of 40 students did not use the mind mapping method. The Torrance Tests of Creative Thinking-Figural (TTCT-F) and Torrance Creative Personality Self-Report Scale were used three times over the 16-week learning period. The results show that learning in the Scratch course promoted the children's creative thinking. The difference between the two groups indicates that mind mapping was beneficial to improve the children's creative thinking.